Natural cordiaquinones as strategies to inhibit the growth and biofilm formation of methicillin-sensitive and methicillin-resistant Staphylococcus spp - De Oliveira, Mariana Araújo; Barros, Ayslan Batista; De Araújo, Gisele Santos; De Araújo, Alyne Rodrigues; Soares, Maria José dos Santos; De Oliveira, Daiane Fernandes; Lima, Filipe Camargo Dalmatti Alves; Batagin-Neto, Augusto [UNESP]; De Almeida Leite, José Roberto de Souza; De Freitas Cesário, Hozana Patrícia Silva; Pessoa, Otília Deusdênia Loiola; Filho, José Delano Barreto Marinho; et al. (Oxford University Press (OUP), 2023)
Aims: The aim of this study was to investigate the antibacterial and antibiofilm potential of cordiaquinones B, E, L, N, and O against different Staphylococci strains, in addition to analyzing in silico the observed effect. Methods and results: The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined according to CLSI guidelines. The inhibition of biofilm formation was investigated at sub-MICs. Atomic force microscopy (AFM) and density functional theory method were performed. The tested strains of Staphylococcus spp. were susceptible to cordiaquinones B, E, and L, among which cordiaquinone B exerted a bactericidal effect, confirmed by a bacterial growth curve study, against Staphylococcus saprophyticus. Cordiaquinones B and E showed lowest MBC values against S. saprophyticus. AFM revealed that cordiaquinone L reduced the mean cell size of S. saprophyticus. Cordiaquinones B and E inhibited the biofilm formation ability of S. aureus by ∼90%. The in silico analysis suggested that the antimicrobial activity of cordiaquinones is driven by their electron donation capability. Conclusions: Cordiaquinones inhibit the growth and biofilm formation (virulence factor) of both methicillin-sensitive and methicillin-resistant Staphylococci strains, indicating their antimicrobial potential. Significance and impact of study This study presents natural cordiaquinones as novel antibacterial and antibiofilm agents against Staphylococcus spp.
Keywords: antibacterial; antibiofilm; Cordia polycephala; cordiaquinones; naphthoquinones